2016
DOI: 10.1007/s12665-016-5297-y
|View full text |Cite
|
Sign up to set email alerts
|

Probability of flooding and vulnerability assessment in the Ajay River, Eastern India: implications for mitigation

Abstract: Estimation of flood intensity for a desired return period is of prime importance for flood management through flood plain zoning. Flood frequency analysis enables estimation of the probability of occurrence of a certain hydrological event of practical importance by fitting a probability distribution to one that is empirically obtained from recorded annual maximum discharge and/or stage data. This case study considers the use of four probability distributions, namely Gumbel's extreme value distribution (EV-I), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In this study, DEM has been processed following standard procedure and after that, it was used for flood-prone area estimation. The calculation for demarcating flood-affected area was done following Bandyopadhyay et al [3]. Extraction of the flood-affected area has been used for 25, 50 and 75 year return period for all models as well as for all the RCPs.…”
Section: Estimation Of the Flood-affected Area And Its Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, DEM has been processed following standard procedure and after that, it was used for flood-prone area estimation. The calculation for demarcating flood-affected area was done following Bandyopadhyay et al [3]. Extraction of the flood-affected area has been used for 25, 50 and 75 year return period for all models as well as for all the RCPs.…”
Section: Estimation Of the Flood-affected Area And Its Mappingmentioning
confidence: 99%
“…A major portion of the world's populations resides in the flood plains and they are indirectly or directly dependent on the flood plains, thereby human encroachment, modification of river and degradation of the ecosystem has become unavoidable results [2]. Along with this, floods are possibly the most frequent, devastating and widespread event, responsible for the huge loss of life and economy [3]. Hwang et al [4] have found that due to global warming, over the past 25 or 30 years of twentieth-century witnessing numerous unprecedented floods globally which have increases the damage rate in a spectacular way [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water related issues in Pakistan are most crucial challenges for the policymakers, hydrologist and water resources engineers in the country (Akhtar, et al, 2008) and extreme flood events are one of the primary natural causes of economic losses in Asia. Natural hazard or calamity and all kind of flood are probably the most frequent and devastating, causing serious loss damages of economic, livelihood of people, and biodiversity (Mohapatra & Singh, 2003;Wang et al, 2011;Sharifi et al, 2012 ;Bandyopadhyay et al, 2016). The probabilities of occurrence of extreme events are determined by frequency analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…(Mazhar Saeed, Ahmad, & Nabi, 2012) workout the flood frequency for Jhelum Basin's homogeneous regions and found Gumbel was the best distribution based on Chi-square test. (Bandyopadhyay et al, 2016) were performed vulnerability assessment in the Ajay River, Eastern India and workout LPT-3 best distribution for flood modeling. The magnitude of the flood was estimated by most affectively distribution Generalized Pareto, and Log Pearson type 3 of different period (Singo, Kundu, Odiyo, Mathivha, & Nkuna, 2012); (Bezak, Brilly, & Šraj, 2014); (Khattak et al, 2016); (Kamal et al, 2016) and, (Benameur, Benkhaled, Meraghni, Chebana, & Necir, 2017).…”
Section: Introductionmentioning
confidence: 99%